Biological and physiological effects of Coriandrum sativum on House fly Musca domestica (Diptera: Muscidae) (Baghdad Science Journal, 2016)
This Study is conducted to evaluate effects of (leaves, fruits) powder and (oil, alcohol) extract of Coriander (Coriandrum sativum) plant on some biological and physiological aspects of House fly, Musca domestica at laboratory conditions. Result show that these preparations caused biological effects represented in high dead percentage in second instar, fed on different concentrations of food treated with them reached to 27.6, 55.3 at concentration 20% of leaf and fruit powder respectively and 67.3, 77.2% at 10% of oil and alcohol extract of fruit, respectively. Furthermore, study also show reduction in pupation and adults emergence percentage. However, leafs powder had slighter effect than powder and extract of fruit of tested plant. The study show physiological effects in treated larvae such as molting failure at subsequent molt to larvae , pupa or to adult, also morphological aberration represented in small size, dark pigment, reduce age and folding of the adult wings. In almost cases, the higher concentration the more morphogenetic aberration. This study leads us to conclude that coriander had chemical compounds which played a negative role in some biological and physiological aspects of house fly.